Pseudo-Monocular Nystagmus Associated with Duane's Syndrome: Report of Two Cases. (3rd July 2015) - Constantinescu, Simona E.; McLean, Rebecca J.; Innes, James; Gottlob, Irene
Abstract: Purpose : To present clinical findings and eye movement recordings of two children who had clinically apparent monocular nystagmus. Methods : Full orthoptic and ophthalmological examination and eye movement recordings. Results : An 8-year-old girl (patient 1) and a 13-month-old girl (patient 2) presented with right monocular nystagmus and right esotropia. A magnetic resonance imaging (MRI) scan of the brain obtained previously had been unremarkable for patient 2. Patient 1 had right amblyopia with visual acuity (VA) reduced to 20/400. Both patients had left abduction deficit and left palpebral fissure narrowing on adduction indicative of Duane's retraction syndrome. Patient 2 also had mild enophthalmos. Both patients had constant horizontal nystagmus in the right eye and very fine nystagmus in the left eye, which could only be detected on video and eye movement recordings. Conclusion : The existence of Duane's syndrome in both patients was masking the presence of nystagmus in the left eye, highlighting that detailed examination in this case can eliminate the need for neuroimaging. Interestingly, the dominant eye of both patients was on the side which was affected by Duane's syndrome, as there was less nystagmus in this eye.